Brazil - Seizing the Opportunity to Compete? - Rodriguez, Alberto (World Bank, Washington, DC, 2012)
Brazil has made considerable progress toward macroeconomic stability since reform measures began to take hold in the early 1990s, and its economy has produced stronger growth as a result-an average of 2.5 percent annually over the past decade. Brazil will have been much better able to take advantage of domestic and international opportunities to spur growth, as did competitors such as China. The Brazilian economy has remained stable as a result of prudent macroeconomic management-including fiscal and monetary policy, as well as debt management. In Brazil, investment in technological innovation comes mainly from the public sector. Brazil invested in research and development infrastructure far earlier than most other developing countries. Acquiring and adapting global knowledge and technology Brazilian firms are just awakening to the full benefits that acquired foreign technology can bring. The report proposes concrete actions in six key areas-the enabling environment, knowledge creation and commercialization, acquisition of foreign knowledge, leveraging and dissemination of technology use, basic education and skills, and tertiary education.